A study of paediatric percutaneous nephrolithotomy in a tertiary care center - Arvind joshi; Punit Tiwari; Roshan Chanchlani (International Journal of Medical Research and Review, 2015)
Aims: To evaluate the technique of Paediatric Percutaneous Nephrolithotomy in terms of safety, outcome and efficacy in age group 1 to 14 years.Material & Methods: The observational study was done from October 2011 to October 2014 in Chirayu Medical College Bhopal. 25 cases of renal stone in paediatric age group were admitted in our hospital and evaluated for size of the stone, number of stones, associated congenital anomalies and complications. PCNL was done by standard technique.Results: A total number of 25 children were operated. Sex distribution in our study was male 15 and female 10, most of the patients were of age group 10-14 years 15(60%). Most of the children15(60%) had large stones >2cm stones and small stone was seen in 6(24%) cases. Malrotated kidney having stone was seen in 8(32%) cases. Complications as fever and haematuria was observed in 1 (4%) case. The maximum sheath size used inchildren was 24 F. Out of 25 children, only one patient required blood transfusion.Conclusion: Paediatric PCNL is safe procedure in expert and experienced hands. Minimal invasive procedures are beneficial in paediatric age group because of longer life expectancy andmore riskof recurrence.